2009
DOI: 10.1037/a0012400
|View full text |Cite
|
Sign up to set email alerts
|

Mentoring students and professionals with disabilities.

Abstract: Mentoring can have a significant positive impact on the lives of individuals. People with disabilities seeking to locate mentors face a variety of potential challenges and benefits. This article addresses mentoring-related issues faced by professionals with disabilities. The article presents a model of mentoring and discusses the difficulties faced by individuals with disabilities in locating mentors. It describes the negative impact of the lack of available mentors upon the educational and vocational developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 19 publications
2
24
0
Order By: Relevance
“…This is important as learning the appropriate form of language when talking with an individual with a disability can potentially improve the behavior and attitudes of mentees towards mentors (Feldman et al 2002 ). Studies have also shown the need for mentors to be trained on encouraging mentees to talk about their disability, to dispel biases and assumptions (Rhodes et al 2009 ), which can hamper the quality of the relationship (Daughtry et al 2009 ). Having more knowledge of their disability can aid this process.…”
Section: Discussionmentioning
confidence: 99%
“…This is important as learning the appropriate form of language when talking with an individual with a disability can potentially improve the behavior and attitudes of mentees towards mentors (Feldman et al 2002 ). Studies have also shown the need for mentors to be trained on encouraging mentees to talk about their disability, to dispel biases and assumptions (Rhodes et al 2009 ), which can hamper the quality of the relationship (Daughtry et al 2009 ). Having more knowledge of their disability can aid this process.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to brain injury, disability may arise from either an acquired illness or injury, or a progressively degenerative disorder (Daughty et al, 2009). Acquired brain injury occurs after a normal period of development and is due…”
Section: Setting the Scenementioning
confidence: 99%
“…There is a vicious cycle for persons with disabilities interested in STEM. 12 Many do not achieve their educational goals and become underemployed or unemployed. The April 2018 labor force participation rate for persons with disabilities in the United States is only 20.9% with an 8.0% unemployment rate, compared to 68.3% and 3.5%, respectively, for people without disabilities.…”
Section: Factors Influencing Decreased Participation Of Persons Withmentioning
confidence: 99%